2022
DOI: 10.3390/ma15103614
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on the Optimization of Femtosecond Laser Treatment on the Surface Morphology of Lithium Disilicate Glass-Ceramics and Highly Translucent Zirconia Ceramics

Abstract: All-ceramic restorations have become increasingly popular in dentistry. Toward ensuring that these restorations adhere to the tooth structure, this study determines the optimal femtosecond laser (FL) treatment parameters for lithium disilicate glass-ceramics and highly translucent zirconia ceramics with respect to surface morphology. For both the ceramics, the following surface conditions were investigated: (1) as-sintered; (2) Al2O3 sandblasted; (3) FL treatment (dot pattern with line distances of 14, 20, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The findings revealed similar morphological aspects for both glass ceramic and zirconia considering the surface modification parameters. The laser-textured surfaces with crossed-line patterns at a distance of 20 or 40 µm revealed a great potential for further studies [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings revealed similar morphological aspects for both glass ceramic and zirconia considering the surface modification parameters. The laser-textured surfaces with crossed-line patterns at a distance of 20 or 40 µm revealed a great potential for further studies [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The surface modification of implants and prosthetic structures by high intensity laser irradiation has gathered attention to improve roughness and wettability for adhesion to resin-matrix cements [7,10,[12][13][14][15]. Currently, different morphological surface features (i.e., micro-grooves, cross-lines, pits, valleys, and peaks) can be produced on ceramics and glass ceramics by using different laser intensity, type, time, and frequency [7,10,[12][13][14][15][16][17]. Previous studies have reported the surface modification of zirconia leading to an increased roughness after short (mili-to nano-seconds) or ultra-short (pico-to femtoseconds) periods of time (pulses) using different types of lasers such as Nd:YAG, Er:YAG, CO 2 , Er,Cr:YSGG, and Nd:YVO 4 [7,10,[12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation